Electrochemically enabled (3+2) cycloaddition of unbiased alkenes and β-dicarbonyls - Suryawanshi, Sharad M.; Sahoo, Suman; Shaligram, Parth S.; Manna, Narugopal; Samanta, Ramesh C. (Chemical Communications, 2024)
A (3+2) cycloaddition between unbiased alkenes and 1,3-dicarbonyls is accomplished by judicious choice of electrode material and electrocatalyst to access dihydrofuran derivatives. A fluorinated porous carbon electrode with appropriate thickness governs unprecedented reactivity. This methodology eliminates the necessity for any stabilizing group within the alkene substrate. This is a rare example of the annulation of unbiased internal and terminal alkenes with cyclic and acyclic beta-dicarbonyls.
Keywords: 1; 3-DICARBONYL COMPOUNDS; DIHYDROFURANS; FACILE SYNTHESIS

Electrochemical deconstruction of waste polyvinylidene chloride (PVDC) to value-added products in batch and flow - Mishra, Subhadip; Kar, Sourav; Rangappa, Raghavendrakumar; Patil, Prashant; Kadam, Vijay; Chikkali, Samir H.; Samanta, Ramesh C. (Chemistry-A European Journal, 2025)
Chlorinated polymers have made enormous contributions to materials science and are commercially produced on a large scale. These chlorinated polymers could be recycled as chlorine sources to efficiently produce valuable chlorinated compounds owing to their facile release of HCl. Although the thermal stability of PVDC is low compared to PVC, this can be advantageous in terms of easy and fast dehydrochlorination. Herein, we report an efficient electrochemical chlorination using poly(vinylidene chloride) (PVDC) as a chlorine source that works in an undivided cell and applies to a good number of examples. This method works on commodity polymers such as waste PVDC-PVC pharma blister film, PVDC-PO multilayer food packaging, and compression molded sheets of Ixan PVDC (with heat stabilizer) with similar efficiency. Furthermore, this method also provides the dechlorination of PVDC up to 98 %, leading to unsaturated dechlorinated material. Converting PVDC into more stable unsaturated compounds, the release of harmful chlorine-containing gases during incineration can be minimized. Additionally, this method is not only restricted to batch processes but an electroflow process for PVDC dechlorination and electrosynthesis has also been demonstrated.
Keywords: chlorination; Electrochemical recycling; Electroflow-synthesis; Graphitic material; Polyvinylidene chloride

Electrochemical generation of N-centered radicals and their reactivity toward cyclization and subsequent C―C bond cleavage - Suryawanshi, Sharad M.; Singh, Mayuri; Samanta, Ramesh C. (Helvetica Chimica Acta, 2026)
N-containing heterocycles are widely used in medicinal chemistry, and they can be synthesized efficiently by the intramolecular cyclization of N-centered radicals. Furthermore, N-centered radicals also act as excellent hydrogen atom transfer (HAT) reagents. On the other hand, nitrogen atoms in the nitrogen-containing heterocycles are used as a handle to cleave stable five and six-membered rings. However, the electrochemical generation of N-centered radicals and their application in forming heterocycles have been extensively studied. Study beyond cyclization remains largely unexplored; in this manuscript, we summarize our new findings as follows. Under electrochemical conditions, the N & horbar;H bond is cleaved, forming an N-centered radical that adds to the double bond in a 6-endo-trig cyclization fashion. The newly formed C-centered radical reacts with oxygen and undergoes C & horbar;C bond cleavage to form the corresponding carbonyl compounds. The reactivity is dependent on the substituents present on nitrogen. In the case of aromatic amine-derived amide, the TEMPO trapping cyclization product was isolated. A mechanism has been proposed to explain the formation of the products.
Keywords: C-C bond cleavage; cyclization; N-centered radical; N-heterocycles; oxidative ring opening

Unveiling the electrochemical reactivity of urethane toward different bond formations and application to polyurethane deconstruction via C―N bond formation - Singh, Adarsh; Samanta, Ramesh C. (Angewandte Chemie-International Edition, 2026)
Plastics are essential, and their production is increasing. The rate of plastic recycling is extremely low, and end-of-life plastics are sent to landfills and oceans, which is alarming. Mechanical recycling is not a viable solution because it produces downgraded materials. Efficient methods for chemical recycling of plastics are essential. Polyurethane is a widely used plastic, and the presence of very stable carbamate functionality makes its recycling extremely difficult. Existing methods require expensive reagents and harsh reaction conditions, such as high temperature, high pressure, and precious metal catalysts such as iridium and ruthenium. Electrochemistry can potentially be used to develop sustainable methods that can operate under milder conditions using fewer reagents. We disclose that urethane serves as an efficient carbamoylation reagent under electrochemical conditions at lower temperatures to form C & horbar;N, C & horbar;P, and C & horbar;C bonds. This method works successfully to deconstruct commercially available polyurethane using different amines. Furthermore, the robustness of the method has been tested on daily life plastics made of polyurethane with additives, such as flexible tubing and mobile covers. This method has also been applied for polymer backbone editing by converting the urethane linkage to urea upon reaction with diamine.
Keywords: carbamoylation; electroreduction of carbamate; polymer upcycling; polyurethane deconstruction; sustainabiliy